2007
DOI: 10.4161/cc.6.23.4957
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated LIM Kinases Colocalize with Gamma-Tubulin in Centrosomes During Early Stages of Mitosis

Abstract: LIM kinases (LIMK1 and LIMK2) are LIM domain containing serine/threonine kinases that modulate reorganization of actin cytoskeleton through inactivating phosphorylation of cofilin. The Rho family of small GTPases regulates the catalytic activity of LIMK1 and LIMK2 through activating phosphorylation by ROCK or by p21 kinase. Recent studies have suggested that LIMK1 could play a role in modulation of cellular growth by alteration of the cell cycle in breast and prostate tumor cells; however, the direct mitogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
(34 reference statements)
3
29
0
Order By: Relevance
“…This study also partly explains our recent observation showing localization of pLIMK1 T508 to the centrosomes during prophase through telophase. 40 In this study, we noted that pLIMK1 T508 colocalizes with Aur-A to the centrosomes during mitosis. At the centrosomes, upon activation through autophosphorylation at T 288 , Aur-A phosphorylates a number of proteins, including LATS2, 60 NDEL 25 for centrosome maturation, kinesin motor protein Eg5, 61 MCAK 62 for spindle bipolarity and ASAP 63 for spindle formation.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This study also partly explains our recent observation showing localization of pLIMK1 T508 to the centrosomes during prophase through telophase. 40 In this study, we noted that pLIMK1 T508 colocalizes with Aur-A to the centrosomes during mitosis. At the centrosomes, upon activation through autophosphorylation at T 288 , Aur-A phosphorylates a number of proteins, including LATS2, 60 NDEL 25 for centrosome maturation, kinesin motor protein Eg5, 61 MCAK 62 for spindle bipolarity and ASAP 63 for spindle formation.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we showed that phosphoLIMK1 (T 508 )(pLIMK1) colocalized with γ-tubulin to the centrosomes during early prophase till early telophase, while nonphosphorylated LIMK1 did not localize to the centrosomes. 40 To further elucidate the involvement of LIMK1 during early mitotic phases, we examined the correlative expression pattern of LIMK1 and Aur-A, which is involved in recruitment of γ-tubulin to the centrosomes during early prophase, 23 in PC-3 cells. Immunofluorescence analysis (IFA) showed strong colocalization of pLIMK1 with Aur-A at the centrosomes during early prophase (Fig.…”
Section: Limk1mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that LIMK regulates cell cycle via regulation of actin cytoskeleton [14,15]. Dynamic alteration of microfilamental structure is very important in cell invasion, movement, adhesion and change in morphology.…”
Section: Discussionmentioning
confidence: 99%